Lessons in Self-Defense: Gender Violence, Racial Criminalization, and Anticarceral Feminism - Thuma, Emily (Women's Studies Quarterly, 2015)
Keywords: 1900-1999; 1980-1989; afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; féminisme autochtone; féminismes noirs; histoire; injustice; intersectionnalité; militance; patriarcat; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; résistance; sciences humaines; systèmes d'oppressions; thématiques; viol; violences; violences d'état; violences sexistes et sexuelles; états-unis; études de genres

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis